The Development and Validation of Collegial Supervisory Practices Questionnaire for Malaysian Public Secondary School Teachers - Hashim, Azmir; Berhandden Musah, Mohammed; Mohd Tahir, Lokman; Jafri, Hadijah; Mohd Yusof, Sanitah; Ahmad, Jamilah; Azean Atan, Noor; Talib, Rohaya (International Journal of Psychosocial Rehabilitation, 2020)
This study develops and validates the scales of collegial supervisory practices of public secondary school teachers in Malaysia. The study uses a quantitative approach to collect data from 357 Malaysian public secondary school teachers. The study employed the Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) to evaluate the internal consistency and psychometric properties of the collegial supervision scales as perceived by public secondary school teachers. The results of PCA revealed five factors with internal coefficiencies ranging from 0.89 to 0.95, which indicated high reliability values across the extracted factors. Furthermore, the results are imperative for being the first of its kind in addressing the standard instrument for collegial supervisory practices in the context of Malaysian public secondary schools.